2019
DOI: 10.1136/gutjnl-2018-317645
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell niche factors secreted from cancer-associated fibroblast by loss of H3K27me3

Abstract: ObjectiveCancer-associated fibroblasts (CAFs), a major component of cancer stroma, can confer aggressive properties to cancer cells by secreting multiple factors. Their phenotypes are stably maintained, but the mechanisms are not fully understood. We aimed to show the critical role of epigenetic changes in CAFs in maintaining their tumour-promoting capacity and to show the validity of the epigenomic approach in identifying therapeutic targets from CAFs to starve cancer cells.DesignTwelve pairs of primary gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 57 publications
1
50
0
Order By: Relevance
“…For instance, cancer-associated myofibroblasts (CAMs, also known as cancer-associated fibroblasts, or CAFs) from GC consistently displayed increased expression of Wnt5a, compared to adjacent tissue myofibroblasts (ATMs) . More recently, a study comparing the methylation and trimethylation (H3K23me3) patterns between CAFs and non-CAFs also identified WNT5A as a target for H3K23me3 predominantly in CAFs and corroborated that CAFs secreted more WNT5A than GC cell lines (Maeda et al, 2019). More importantly, this report showed that, in histological samples, WNT5A had higher expression in fibroblasts (which were identified by α-SMA staining), compared to cancer cells (Maeda et al, 2019).…”
Section: Wnt5a Expression In Gastric Cancersupporting
confidence: 52%
“…For instance, cancer-associated myofibroblasts (CAMs, also known as cancer-associated fibroblasts, or CAFs) from GC consistently displayed increased expression of Wnt5a, compared to adjacent tissue myofibroblasts (ATMs) . More recently, a study comparing the methylation and trimethylation (H3K23me3) patterns between CAFs and non-CAFs also identified WNT5A as a target for H3K23me3 predominantly in CAFs and corroborated that CAFs secreted more WNT5A than GC cell lines (Maeda et al, 2019). More importantly, this report showed that, in histological samples, WNT5A had higher expression in fibroblasts (which were identified by α-SMA staining), compared to cancer cells (Maeda et al, 2019).…”
Section: Wnt5a Expression In Gastric Cancersupporting
confidence: 52%
“…During tumor progression, this microenvironment develops anatomically distinct "niches", leading to enrichment of a small population of "stem-like" cells that have a distinct survival advantage over the bulk of the tumor cells. This population contributes to the aggressive biology of the disease [2][3][4] . Our previous studies show that this aggressive population has increased selfrenewal properties (contributing to tumor recurrence), increased invasiveness, and ability to evade adverse chemotherapeutic assault on the tumor and is represented by the expression of CD133 on their surface 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, enhancement of antigenicity of tumor cells by activation of endogenous retroviruses [ 18 , 19 ] was found to be an important mode of action. Recently, in addition to the effect on tumor cells, that on tumor cell niche, including cancer-associated fibroblasts and myeloid-derived suppressor cells (MDSCs) has been suggested also to be involved [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%